Sensing Non-sense in Animal Sex From Perspective of Transposable Elements - Mukherjee, Ayan (Animal Reproduction Update, 2021)
The evolution of vertebrate species took shape through millions of years, where sex played an important role in maintenance of a lineage, genetic diversification and reproductive isolation. On due course of sexual evolution, sex determination strategies have been proposed to flow from temperature dependent sex determination to genetic sex determination, which has been demonstrated as XY system in mammals and ZW system in birds. In contrary to this established conception, different lineages showed to have overlapping sex-determining strategies. While searching possible reasons for these phenomenons, researchers observed that gene content of sex chromosomes is highly variable as far as their location and prevalence is concerned, which otherwise suggested autosomal origin of sex chromosomes. Although the exact mechanisms of gene transfer and thereby origin of sex chromosomes are yet to be unveiled, but chromosomal rearrangement and introgression has been hypothesized to be the possible effector. Transposable elements (TEs) are long been considered to be ‘Selfish’ or ‘Junk’ DNA material as most of the non-coding genomic regions are comprised by TEs, which did not make any sense to be a part of species genome. But recently, TEs are being considered to be a nature’s tool for biological innovation by creating new regulatory elements, new coding sequences, genetic disruption and chromosomal remodelling. So, this has been postulated that TEs could facilitate rearrangement and introgression, which ultimately lead to evolution of sex chromosomes and sex determining genes through positive selection. Prevalence of highly repetitive sequences in sex chromosomes, particularly in Y, makes it a hot bed for TEs mediated rearrangement and introgression. In this review, I tried to discuss whether it makes any sense to focus on the role of TEs in sexual evolution of animals.
Keywords: Transposable Elements; Evolution; Sex Chromosomes